Pottery spilled the beans: Patterns in the processing and consumption of dietary lipids in Central Germany from the Early Neolithic to the Bronze Age. - Adrià Breu; Roberto Risch; Elena Molina; Susanne Friederich; Harald Meller; Franziska Knoll (PLoS ONE)
The need to better understand economic change and the social uses of long-ago established pottery types to prepare and consume food has led to the study of 124 distinct ceramic vessels from 17 settlement and funerary sites in Central Germany (present day Saxony-Anhalt). These, dated from the Early Neolithic (from 5450 cal. BCE onwards) to the Late Bronze Age (1300-750 cal. BCE; youngest sample ca. 1000 BCE), include vessels from the Linear Pottery (LBK), Schiepzig/Schöningen groups (SCHIP), Baalberge (BAC), Corded Ware (CWC), Bell Beaker (BBC), and Únětice (UC) archaeological cultures. Organic residue analyses performed on this assemblage determined the presence of vessel contents surviving as lipid residues in 109 cases. These were studied in relation to the changing use of settlement and funerary pottery types and, in the case of burials, to the funerary contexts in which the vessels had been placed. The obtained results confirmed a marked increase in the consumption of dairy products linked to innovations in pottery types (e.g., small cups) during the Funnel Beaker related Baalberge Culture of the 4th millennium BCE. Although the intensive use of dairy products may have continued into the 3rd millennium BCE, especially amongst Bell Beaker populations, Corded Ware vessels found in funerary contexts suggest an increase in the importance of non-ruminant products, which may be linked to the production of specific vessel shapes and decoration. In the Early Bronze Age circum-Harz Únětice group (ca. 2200-1550 BCE), which saw the emergence of a highly hierarchical society, a greater variety of animal and plant derived products was detected in a much more standardised but, surprisingly, more multifunctional pottery assemblage. This long-term study of lipid residues from a concise region in Central Europe thus reveals the complex relationships that prehistoric populations established between food resources and the main means to prepare, store, and consume them.